Effect of Processing Methods on the In Vitro Protein Digestibility and Vitamin Content of Edible Winged Termite (Macrotermes subhylanus) and Grasshopper (Ruspolia differens) - Kinyuru, John N.; Kenji, Glaston M.; Njoroge, Simon M.; Ayieko, Monicah (Springer, 2010)
The influence of processing methods of toasting and solar drying on the in vitro protein digestibility and vitamins content of edible winged termites, green grasshoppers, and brown grasshoppers consumed in Siaya, district of Kenya, was determined using standard methods. Analysis was done on fresh, toasted, toasted dried, and fresh dried insect samples. There was no significant change (p > 0.05) in protein digestibility in the termite samples, while a significant decrease (p ≤ 0.05) in the grasshopper samples was observed on toasting and drying. There was a significant reduction (p ≤ 0.05) in riboflavin content with 4.18 mg/100 g in fresh termites, 2.76 mg/100 g in toasted termites, 2.26 mg/100 g in fresh dried termites, and 1.50 mg/100 g in toasted dried termites on processing. There was also a significant reduction (p ≤ 0.05) in niacin content in the grasshoppers with 3.61 mg/100 g in fresh green grasshopper, 3.28 mg/100 g in toasted green grasshopper, 3.22 mg/100 g in fresh dried green grasshoppers, and 3.06 mg/100 g in toasted dried green grasshoppers. A significant reduction (p ≤ 0.05) in retinol content with 2.24 μg/g in fresh termites, 1.56 μg/g in toasted termites, 1.02 μg/g in toasted dried termites, and 0.98 μg/g in fresh dried termites was also reported. The processing methods of the insects affected their nutrient potential as evidenced by the changes in protein digestibility and vitamins content. Therefore, optimal processing methods need to be investigated even as we promote commercialization of these insects.
Keywords: Processing; Edible insects; Protein digestibility; Vitamin